Exposing Differences in Monomer Exchange Rates of Multicomponent Supramolecular Polymers in Water. Issue 3 (23rd December 2015) - Baker, Matthew B.; Gosens, Ronald P. J.; Albertazzi, Lorenzo; Matsumoto, Nicholas M.; Palmans, Anja R. A.; Meijer, E. W.
Abstract: The formation of multicomponent and bioactive supramolecular polymers is a promising strategy for the formation of biomaterials that match the dynamic and responsive nature of biological systems. In order to fully realize the potential of this strategy, knowledge of the location and behavior of bioactive components within the system is crucial. By employing synthetic strategies to create multifunctional monomers, coupled with FRET and STORM techniques, we have investigated the formation and behavior of a bioactive and multicomponent supramolecular polymer. By creating a peptide‐dye‐monomer conjugate, we were able to measure high degrees of monomer incorporation and to visualize the equal distribution of monomers within the supramolecular polymer. Furthermore, by tracking the movement of monomers, we uncovered small differences in the dynamics of the bioactive monomers. Abstract : Tracking your monomers : Differences in behavior and dynamics are revealed by labeling bioactive monomers and tracking them within a multicomponent supramolecular polymer. These methods and observations are essential to facilitate control over monomer distribution and location in future generations of supramolecular biomaterials.